Glucosyltransferase activity-based screening identifies tannic acid as an inhibitor of Streptococcus mutans biofilm - Xu, Mai; Wang, Xinyan; Gong, Tao; Yang, Ziyi; Zhang, Dian; Ma, Qizhao; Li, Yuqing (Frontiers in Microbiology, 2025)
Dental caries is a biofilm-related chronic infectious disease. Streptococcus mutans is the core microorganism that leads to caries, with its capacity to form biofilms via glucosyltransferases (Gtfs) being the predominant virulence factor contributing to this condition. Therefore, researching novel drugs targeting Gtf is important for treating dental caries. Our study established a rapid detection method for Gtf activity to screen over 1,000 compounds from the Selleck Natural Product Library. We identified tannic acid (TA) as a potential inhibitor of Gtf activity. In vitro experiments suggested that TA could inhibit extracellular polysaccharide (EPS) synthesis and biofilm formation in S. mutans by selectively antagonizing Gtf rather than directly killing the bacteria. Molecular docking experiments confirmed a strong binding affinity between TA and Gtf. In summary, TA exhibits good anti-virulence performance against S. mutans, indicating its potential value in anti-biofilm and anti-caries applications.